Angiomatoid fibrous histiocytoma: a series of seven cases including genetically confirmed aggressive cases and a literature review. Issue 1 (December 2017) - Saito, Kenichi; Kobayashi, Eisuke; Yoshida, Akihiko; Araki, Yoshihiro; Kubota, Daisuke; Tanzawa, Yoshikazu; Kawai, Akira; Yanagawa, Takashi; Takagishi, Kenji; Chuman, Hirokazu
Abstract Background Angiomatoid fibrous histiocytoma (AFH) is a rare soft tissue tumor of intermediate biologic potential. Because of its rarity and nonspecific radiological and diverse pathological findings, AFH is often clinically misdiagnosed. However, few clinical reports have described this tumor. As reported herein, we analyzed the clinical and radiological features and clinical outcomes of AFH. Methods We retrospectively reviewed the medical records of seven cases histopathologically diagnosed as AFH. We examined clinical features, MRI findings, histopathological diagnoses, treatments, and outcomes. Results These seven cases comprised five male and two female patients with ages ranging from 8 to 50 years old. The primary locations included upper extremities in 2, lower extremities in 4, and the inguinal region in one patient. Of the tumors, 4 occurred in subcutaneous tissues and 3 occurred in deep tissues. No cases were diagnosed as AFH from MRI and needle biopsy results. All cases were diagnosed histopathologically after excision. After treatment, 2 patients (29%) had tumor recurrence and metastasis, one of whom died from disease progression. These 2 aggressive cases involved both EWSR1 and CREB1 gene rearrangements as determined by FISH. The other patients were alive and well without recurrence or metastasis. Conclusion AFH is a rare tumor that is difficult to diagnose. Therefore, it tends to be misdiagnosed and to be treated inadequately by referring physicians. Surgeons must therefore be mindful of the presence of AFH, learn about appropriate treatment necessary for this tumor, and conduct careful follow-up because AFH can engender poor outcomes.